Programa educativo “jhosy” para el mejoramiento de la producción de textos narrativos en estudiantes de segundo grado de secundaria en la Institución Educativa Simón Bolivar, Iquitos 2022 - Huanuiri Mattos, Jhosefany Angells (2024)
The purpose of the study was to evaluate the effect of the educational program “JHOSY” to improve the production of narrative texts in second grade high school students at the Simón Bolívar Educational Institution. Experimental, quasi experimental study of two groups with 35 students each. He used the performance test valued by a rubric. The results of the EG posttest, there was an improvement in the production of narrative texts with averages of 15.37; frequent value 16, dispersing the information into 1,114 points according to its average. Likewise, the planning indicators increased by 1.57 points, their average being 3.0 points; Textualization increased its score by 4.71 points, with an average of 8.71 points. Evaluation increased 2.06 points, reaching its average of 3.63 points. It concluded: The application of the educational program “JHOSY” improved the elaboration of narratives in second grade secondary school students of the Simón Bolívar Educational Institution” (Wilcoxon= 630; contrast statistic t=5.177; with p= 0.000<0.05)